The social values derived from divorce and its educational applications - Al-Ansari, Samer Mohammed (Journal of Islamic Sciences, 2019)
This study deals with the social values ​​that were unique to Surat Al-Talaq, through an objective study, and between Surat Al-Talaq in its subjects and the issues it dealt with in order to stand on the impact of Sura. The method was followed by the deductive approach, which consisted of studying the whole sura and then selecting a collection of verses in a selective manner. The verses were then divided into sections in line with the objectives of the study. The books of interpretation were also consulted and the books of education were devised to develop these values. Study with a set of results: • Surat al-Talaq (Surat al-Talaq) is one of the surahs that has specialized in the subject of divorce in detail and has not been repeated in the other chapters • Sura divorce is of great importance in the affairs of the Muslim family with its different emotional, emotional and psychological aspects. • The study of the Holy Quran for the specialist in education opens up important educational horizons to him, from which he can draw scientific and practical contents that expand his theoretical and applied balance and enhance his culture. • Repetition is one of the most important educational methods mentioned in Sura, which is useful in establishing the information and in the speed of remembering it. • To assume the responsibility entrusted to the human right to do, both towards himself or his dependents, guarantees him the victory and survival in the world and the hereafter. • Sura showed the fact of punishment on the work, it is better part of the good, and those who hurt his punishment painful punishment